Computational Modeling of the Amperometric Bioanalytical System for Lipase Activity Assay: a Time-Dependent Response - Puida, M.; Ivanauskas, F.; Ignatjev, I.; Valinčius, G.; Razumas, V. (Nonlinear Analysis: Modelling and Control, 2007)
This paper presents computational modeling of response kinetics of bioelectroanalytical system based on the interfacial action of enzyme lipase. The model also assumes that the substrate of enzyme is located on the surface of micelles which are spread in the solution under study. Two distinct mathematical models have been developed and evaluated through computational simulation series. The results of simulation demonstrate that diffusion is important factor for the sensitivity of bioelectroanalytical system, and it is important to take this process of mass transfer into account in all system areas.